Decoding Motivation : Verbal & Visual Signification In Sport Posters Discourse - Deni Krisnawan; Desak Putu Eka Pratiwi (Lingual: Journal of Language and Culture, 2025)
This study aims to analyze the semiotic elements found in motivational sport posters by examining how verbal and visual signs construct motivational meaning. Drawing on semiotic theories by Chandler (2007), Barthes (1968), and Cerrato (2012), the study explores how texts, images, and colors function to evoke values such as passion, discipline, and determination in a sporting context. Data were collected from Pinterest through observation and note-taking methods. Verbal signs such as motivational slogans and visual signs including athlete imagery, color schemes, and body language were classified and analyzed based on their denotative and connotative meanings. The findings reveal that motivational sport posters use a synergistic combination of visual and verbal cues to influence viewer emotion and behavior. This research contributes to the understanding of how motivational messages are constructed and interpreted within visual communication, particularly in sports culture.